TEATRIKAL MAKROEKONOMISME GLOBALISASI - Wahyudi, Fendy Eko (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Globalization has been seen as the main power of development. it becomes the buzzword of economic advancement. The success story of several countries including China, India, and also Indonesia being noted as the good side of Globalization. The main theme of my paper is on globalization and equality. Further, question for consiedaration in this paper I discussed wether globalization enhance economic inequality. By reviewing several indicators that used to be seen as the indicator of globalization of economic, hence put more emphasis on more micro-economics indicators I argue that globalization actually endager economic equality. the â€œfairy taleâ€ of globalization economic prosperity arise due to the using of â€œtheatrical macro economicsâ€ Indicators. In a nutshell this macro-economics indicator conceals the real face of globalizationâ€™s economic consequences.